THE EFFECTIVENESS OF NUTRITION EDUCATION IN IMPROVING NUTRITION KNOWLEDGE AMONG HIGH SCHOOL STUDENTS: A STUDY AT SMAN 1 MARGAHAYU - Rohima, Ira Endah; Inayah, Istiyati; Triani, Rini; Zahra, Nabilah; Hermawan, Cindy Zahra Putri; Maskati, Bassam Shauqi; Nurullah, Dzakirah Asma; Al-Farizi, Jidan (LPPM Univ. Ibn Khaldun Bogor, 2025)
Adolescent nutrition remains a major public health concern in Indonesia, with issues such as anemia, undernutrition, and obesity often linked to limited dietary knowledge. This study aimed to evaluate the impact of nutrition education on the knowledge level of high school students. A total of 325 students from SMAN 1 Margahayu, Bandung Regency, participated in a pre-test and post-test using a 12-item multiple-choice questionnaire assessing basic nutrition concepts, nutrient functions, and balanced diet principles. The results showed that in the pre-test, 83.08% of students demonstrated good knowledge, 13.23% were categorized as fair, and 3.69% as poor. Following the nutrition education intervention, the proportion of students with good knowledge increased to 91.78%, while those in the fair category decreased to 8.22% and none remained in the poor category. These findings indicate that nutrition education was effective in improving students’ knowledge and highlight the importance of school-based nutrition programs to strengthen adolescent awareness and understanding of balanced nutrition.